Transcatheter Aortic Valve Implantation in Heart Failure Patients with Non-Severe Aortic Valve Stenosis - Amr Elkammash (Ital Publication, 2022)
Introduction: aortic stenosis (AS) increases the afterload on the left ventricle, leading to structural changes in the heart muscle and gradual progression to heart failure (HF). The clinical guidelines recommend aortic valve replacement (surgical or transcatheter) in patients with HF and severe AS. The evidence on the benefits of Transcatheter aortic valve implantation (TAVI) for patients with less-than-severe AS and HF is still controversial and inconclusive. Methods: the literature was systematically searched on three different scientific databases (PUBMED, Google Scholar, EMBASE) using different combinations of search words (heart failure, non-severe aortic stenosis, less-than-severe aortic stenosis, mild to moderate aortic stenosis, TAVI, TAVR). Results: in heart failure patients, observational studies showed a significant reduction in mortality using TAVI to manage non-severe aortic stenosis compared to medical treatment. However, evidence from randomized controlled trials is still lacking. Conclusion:HF increases the surgical risk of AS patients; therefore, TAVI represents a safer option. The preliminary results indicated the benefit of TAVI in managing AS in HF patients, even if the AS did not reach the severe stage.   Doi: 10.28991/SciMedJ-2022-04-04-05 Full Text: PDF